NEUROSCIENCE IN DEVELOPING STUDENTS' INTELLECTUAL INTELLIGENCE OF AL-AZHAR ISLAMIC PRIMARY SCHOOL - Susanto Susanto; Ida Royani Munfarokhah (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:Neuroscience in developing students' intellectual intelligence is crucial to know by teachers. The nervous system structure is an aspect that underlies human actions both from cognitive, affective, and psychomotor aspects. This research aimed to find out information related to neuroscience in developing students' intellectual intelligence of Al-Azhar Islamic Primary School Bumi Serpong Damai. This research was qualitative research using a phenomenological approach. The subjects were one principal as a supporting informant, five teachers, and the students of 1 to 6 grades. The data were analyzed to interpret the data into information so that the data's characteristics or properties can be easily understood and useful to answer problems related to research activities. The results showed that neuroscience could grow the students’ attention, develop an active and creative learning model, consider the diversity of brain development of students, develop fun learning stimulation, and create positive emotions.Abstrak:Ilmu saraf dalam mengembangkan kecerdasan intelektual siswa sangat penting untuk diketahui oleh guru. Struktur sistem saraf merupakan aspek yang mendasari tindakan manusia baik dari aspek kognitif, afektif, dan psikomotorik. Penelitian ini bertujuan untuk mengetahui informasi yang berkaitan dengan ilmu saraf dalam mengembangkan kecerdasan intelektual siswa di Sekolah Dasar Islam Al-Azhar Bumi Serpong Damai. Penelitian ini merupakan penelitian kualitatif dengan pendekatan fenomenologi. Subjek penelitian ini adalah satu kepala sekolah sebagai informan pendukung, lima orang guru, dan siswa kelas 1 sd 6. Data dianalisis untuk menginterpretasikan data menjadi informasi sehingga sifat atau sifat data dapat dengan mudah dipahami dan berguna untuk menjawab permasalahan yang berkaitan dengan kegiatan penelitian. Hasil penelitian menunjukkan bahwa ilmu saraf dapat menumbuhkan perhatian siswa, mengembangkan model pembelajaran yang aktif dan kreatif, mempertimbangkan keberagaman perkembangan otak siswa, mengembangkan stimulasi belajar yang menyenangkan, dan menciptakan emosi yang positif.